Cerebral amyloid angiopathy-related inflammation (CAA-ri) in a patient positive for SARS-CoV-2 – radiological findings and differential diagnosis - Dębicka, Marta (Wiedza Medyczna, 2021)
84-year old female with confirmed, asymptomatic SARS-CoV-2 infection was admitted to Neurology Department after sudden onset of left-sided hemiparesis and impaired consciousness. Imaging played a key role in diagnostic process, in course of which the diagnosis of cerebral amyloid angiopathy-related inflammation (CAA-ri) was made. According to latest research, SARS-CoV-2 infection is considered to cause various neurological complications. To my best knowledge this is the first case of CAA-ri and SARS-CoV-2 coexistence to be reported.